Alternative strategic financial plans for Garden City Co-op - Brant, Barry (Kansas State University, 2008)
The goal of this thesis is to evaluate future financial strategies for the Garden City Co-op (GCC). The evaluation will include a standard financial analysis of historical financial information and pro forma financial projections of selected strategies. The strategies will be evaluated using management assumptions in which liquidity and solvency are proactively managed. The ultimate goal of the GCC is to return as much profit to its patron-owners as possible but at the same time provided them with the product and services they need for their own business at a competitive level. The GCC has recently experiencing unusually high profits and believes this will be the trend over the next six to eight years due to the business ventures and relationships that currently are in place to grow sales outside the Co-op's traditional trade territories. The increased revenues and profits have come primarily from profitable joint ventures, especially from a very high volume of petroleum sales to non-member patrons. The most critical relationship is member patron-owner relationship with CHS Inc., a large regional cooperative that owns two oil refineries and is the primary supplier of petroleum products to GCC. The profits being made by CHS Inc.'s fuel refineries are distributed to GCC as patronage refunds based on the volume of refined fuels purchased from them. This much larger stream of patronage refunds from CHS and other regional co-op's being distributed to GCC is causing GCC to pause and evaluate how best to move forward. The GCC has the challenge of what to do with increased earnings. Does the GCC return earnings back to its member-owners retain earnings for future investment opportunities, or do they commit them to help finance current investment opportunities? Does GCC grow its most profitable business lines, such as nonmember-nonpatron petroleum sales? Given the close relationship with CHS in terms of income distributions and equity management, including cash patronage refunds and cash equity redemptions of retained patronage refunds, and the close relationship with its own member patron-owners, is its current income distribution and equity management program sustainable under various strategies?
Keywords: Cooperative; Financial; Agriculture; Economic; Strategies Planning; Financial Projections; Agriculture, General (0473); Economics, Agricultural (0503); Economics, Finance (0508)